Perspectivas para o desenvolvimento de uma metodologia brasileira para o BIM: estudo de caso - Rudner Fabiano Lopes (2017)
The construction industry has been facing a paradigm that seems to be positive to increase productivity, efficiency, quality, and the sustainability in products, reducing production costs, minimizing times and duplicated information, using collaboration between many construction disciplines within projects developed in Building Information Modeling (BIM) systems. The technological and methodological migration of many construction disciplines to BIM is imminent in Brazil. Even so the BIM methodology holds itself promise of gains in quality, productivity and sustainability, Brazilian companies have been facing challenges in the implementation process of BIM coping from the inexistence of libraries of national construction components; until the fact that the constructors many times are not enough qualified to promote changes in graphical representation and project reading, or for the utilization of tridimensional information models as references for construction at the build site. Another problems is that BIM software is not adapted to Brazilian norms and calculation methods; there is just a few people trained to the BIM working at Brazil. However, success in BIM implementation at Brazil can be studied in some cases in order to develop a methodology adapted to the national reality of construction. This research aims to study a Brazilian company in its BIM implementation process in order to find new perspectives for a BIM implementation methodology compatible with the national EAC industry. The results shall contemplate a compilation of the real gains and challenges in BIM adoption particularly in Brazil, besides other countries. It also aims to contemplate perspectives for a new national methodology for BIM implementation guided by people, processes and technology capable to cover strategies which supplants the challenges involved in BIM adoption at Brazil.